Desarrollo del Prototipo de Control de acceso a los laboratorios de la Carrera de Computación de la UNL: SmartLab. - Campoverde, Israel Alexander (2023)
Access control to laboratories in the Computer Science career is of vital importance to guarantee the security of resources and to maintain an adequate environment for the development of academic activities. Before the pandemic, an access control with RFID technology was implemented in the laboratory, which presented communication conflicts between the hardware and the web page server. For this reason, the main objective of this Degree Project was to develop an access control prototype using RFID technology and a temperature sensor for the laboratories of the Computer Science career at the National University of Loja, validating the entry of users based on the result of the schedule and their body temperature. To meet the main objective, 3 phases were developed. I) The current situation in the laboratories was analyzed by studying the previous work implemented with RFID. II) The software and hardware module was developed using a temperature sensor based on the Odoo architecture. III). Product acceptance was evaluated using the technology acceptance model. It was identified that, due to the implementation of new security protocols, the registration of entrance to the laboratories has been discontinued. With the information gathered and together with the use of the XP methodology, the web system was developed using Odoo and the hardware part was adapted to the previous prototype with new components for its correct operation, such is the case of the MLX90614 temperature sensor. Finally, the prototype was implemented in the laboratory: software development to evaluate the acceptance of users, the results show that the system has been perceived favorably to security, ease of use and prevention of contagions. Keywords: Odoo, access control, RFID technology, temperature sensor